Biofortified sweet potatoes - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
Vitamin A deficiency affects over 140 million children under the age of five. In the absence of adequate amounts of vitamin A immune systems suffer irreversible damage and blindness occurs. A recent study found that boiled orange-fleshed sweetpotato (OFSP) contained over 1,000 Retinol Activity Equivalents (RAE) per 125 grams, which, when fed to school aged children in South Africa, provided 250 percent of their recommended daily allowance.. At present, Africa’s predominant sweetpotato cultivars are white- or yellow-fleshed varieties that contain small amounts of beta-carotene. By contrast, the [much less common] orange-fleshed varieties are rich sources of beta-carotene. In addition, orange-fleshed varieties are inexpensive and can be grown year-round, making them an ideal source of vitamin A for the poor. If sweetpotato could be bred for local growing conditions, and if sufficient demand was created, farmers and consumers could switch from non-orange to orange-fleshed varieties, thereby making significant progress toward improving vitamin A.